Mineralogical and Petrographic Characterization: An Indication of Fractability of Shale Gas Reservoir in the Blue Nile Basin, Sudan - Monera A Shoieb, Nor Syazwani Zainal Abidin, Chow Weng Sum, Yass, . (2017)
The production of gas and oil that plays an unconventional role in the world has affected the finances and the energy securities. The mineralogical characterization of shale rocks has a significant effect on the efficiency of shale gas, especially for drilling and production operations